Pemanfaatan Media Video Pada Website Dan Youtube Untuk Meningkatkan Kemampuan Toefl Dan Menulis Abstrak Kti Calon Lulusan Unived - Azizatul Banat; Eli Diana; Mariska Febrianti; Filza Ratu Nabila; Wahyu Dirgantara; Putri Mardanis (Jurnal Dehasen Untuk Negeri, 2024)
TOEFL is a Test of English as a Foreign Language which is a test of basic English language skills which is also one of the requirements for prospective graduates at the University of Dehasen Bengkulu. In the last few years after the Covid 19 pandemic, the TOEFL test as a graduation requirement at the University of Dehasen Bengkulu was carried out using Google Forms and information media such as websites and YouTube as intermediary media in conveying important material to prospective graduates. Apart from that, prospective graduates need to be provided with material about the importance of Scientific Writing abstracts which are related to the student's final assignment, namely the thesis. The thesis’s abstract is translated into English at UPT Bahasa Inggris to make it easier for readers to search for research reference titles through the abstract. Apart from this aim, the title of the scientific writing abstract at the University of Dehasen Bengkulu, will be translated as a reference for the thesis title in the English transcript. In the context of community service carried out by a team of lecturers from the Faculty of Teacher Training and Education who collaborated with the UPT English Language Team at the University of Dehasen Bengkulu as managers and organizers of TOEFL and Thesis’s abstract translation which raised the title "Utilization of Video Media on Websites and YouTube to Improve TOEFL Skills and Scientific Writing Abstracts for Prospective UNIVED Graduates". The stages of service activities are carried out starting from preparation, needs analysis, implementation and preparation of activity reports. Delivery of socialization material by utilizing videos uploaded on the UPT Bahasa Inggris website and YouTube channel. Apart from that, the initial introduction to TOEFL was carried out through the Zoom application and WhatsApp Group management. Apart from that, test technical briefings and simulations on the use of Google Form media for the TOEFL test are carried out face-to-face alternately for prospective graduates who have difficulty and do not understand how to operate the LJK Google Form. With this activity, it is expected that there will be increased knowledge and preparation for prospective graduates before taking the TOEFL test and prospective graduates can understand the strategy of scientific writing abstract, then it is expected that this activity will continue in the future.